Mechanisms of C Sequestration in Soils of Latin America - Jiménez, J. J.; Lal, R. (Critical reviews in plant sciences, 2006)
Carbon (C) sequestration, defined as the process whereby atmospheric CO 2 is transferred into a long-lived C pool, is an important issue not only in the scientific community but also in the society at large because of its potential role in off-setting fossil fuel emissions. Through photosynthesis this C is stored in plants and through decomposition, trunks, branches, leaves and roots are incorporated in the soil via the action of different soil organisms, i.e., bacteria, fungi and invertebrates. This, together with the C exudates from roots that are utilized by microbial populations, constitutes the natural pathways of incorporating biomass-C into the soil. The amount of C stored in terrestrial ecosystems is the third largest among the global C pools. Soil organic carbon (SOC) up to 3 m is 2,344 Pg C (1 Petagram = 10 15 g), and the SOC pool in tropical soils is approximately 30% of the global pool. Abiotic factors, which moderate C sequestration in soils are clay content, mineralogy, structural stability, landscape position, and soil moisture and temperature regimes. On the other hand, biotic factors involved in soil C sequestration are determined by the activities of soil organisms. However, models do not include the formation, stabilization and lifespan of the aggregates that have been biologically produced, including roots. This is not only due to the lack of studies on this subject, but also to overlooking the role of soil organisms in soil aggregation. Furthermore, there is a lack of comprehensive knowledge regarding the processes that control dissolved organic carbon (DOC) fluxes in soils and its role in the global budget of C sequestration. The boundaries of ecosystems are not considered in the studies of the subject, as it may be the case for terrestrial C sequestration, since the borders around the sites under study constitute pathways for the flow of C between sites and through the landscape. The concentrations of DOC in deep soil horizons and the contribution to DOC fluxes (exports) are relatively small, from 4 to 37 g DOC m −2 yr −1 retained in the mineral subsoil. In South America, although substantial research has been done under different ecosystems and land use systems in some countries, like Brazil, Colombia, Argentina, there is a need to conduct more studies with agreed standard methodologies in natural ecosystems and agricultural systems, and in other areas of Central America few studies have been undertaken to date. The principal objective of this review was to address the main mechanisms that determine SOC and SIC sequestration in soils of Latin America, and include: physical aggregate protection, SOC-clay interaction, DOC transport, bioturbation by soil organisms, and the formation of secondary carbonates. All of these mechanisms are generally explained by physical and chemical processes. In contrast, this review takes a soil ecological approach to describe the mechanisms listed above.